(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2023)
Today, construction machines are widely used, which can be used in hazardous and toxic working environments, in other adverse environments, and in places where it is very difficult for a human operator to control the machine. At the same time, in the current difficult economic situation, it is important to increase the productivity of these construction machines in the mining, construction, and manufacturing sectors. Due to the versatility and convenience of hydraulically driven manipulators among construction machines, they occupy the majority of equipment used in mining or construction work. Vibration machines are used in many technological processes for the removal of hard rocks and other materials in the work performed by hydraulic excavators. This paper considers a hydraulically driven drilling robot with four degrees of freedom. These are machines and equipment based on lever mechanisms of variable structures, which have a number of advantages over analogs. The use of mechanisms of variable structures significantly increases the reliability of vibration shocks, their design is simple and does not require imported materials and components. This is especially important for machines operating in difficult mountain conditions. Under the above operating conditions, semi-automatic or fully computer-controlled machines can work successfully and efficiently. To do this, it is important to understand the kinematics of this machine. therefore, the article describes the sequence of actions required to solve the direct problem of kinematics directed at a drilling robot with four degrees of freedom.